2022
DOI: 10.34067/kid.0003802021
|View full text |Cite
|
Sign up to set email alerts
|

Shroom3, a Gene Associated with CKD, Modulates Epithelial Recovery after AKI

Abstract: Background: Ischemia induced acute kidney injury (AKI) resulting in tubular damage can often progress to chronic kidney disease (CKD) and is a common cause of nephrology consultation. Following renal tubular epithelial damage, molecular and cellular mechanisms are activated to repair and regenerate the damaged epithelium. If these mechanisms are impaired, AKI can progress to CKD. Even in patients whose kidney function returns to normal baseline are more likely to develop CKD. Genome-wide association studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Interestingly, our analysis suggests that anterior shroom3 crispant cells fail to constrict less from a lack of actomyosin accumulation and more from an inability to accumulate N-cadherin at the medial surface of cells. This is consistent with a previously reported genetic interaction between shroom3 and N-cadherin ( Lang et al, 2014 ; Li et al, 2021 ; Plageman et al, 2011b ), and suggests that a Shroom3-N-cadherin pathway may drive anterior apical constriction during neural tube closure. The function of this N-cadherin remains to be determined, but two possibilities are suggested by prior studies.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, our analysis suggests that anterior shroom3 crispant cells fail to constrict less from a lack of actomyosin accumulation and more from an inability to accumulate N-cadherin at the medial surface of cells. This is consistent with a previously reported genetic interaction between shroom3 and N-cadherin ( Lang et al, 2014 ; Li et al, 2021 ; Plageman et al, 2011b ), and suggests that a Shroom3-N-cadherin pathway may drive anterior apical constriction during neural tube closure. The function of this N-cadherin remains to be determined, but two possibilities are suggested by prior studies.…”
Section: Resultssupporting
confidence: 92%
“…9 Following acute kidney injury, Shroom3 heterozygous knockout mice displayed increased mortality, worsened kidney function, and heightened fibrosis. 10 Studies in different animal models show similar results: post-natal Shroom3 knockdown induces albuminuria in mice, reintroducing the normal Shroom3 gene into hypertensive rats alleviates albuminuria and glomerulosclerosis, and introducing wild-type Shroom3 into Shroom3 -deficient zebrafish remedies glomerular abnormalities. 11,12 Despite these insights, the comprehensive impact of the SHROOM3 gene on kidney disease, relevant biomarkers, and underlying mechanism remains incompletely understood.…”
Section: Introductionmentioning
confidence: 85%
“…35,55 Additional studies confirm consistency in protein expression in some, but not all, epithelial cells in the apical regions of the initial S1 segment of the proximal tubule, distal convoluted tubule, and medullary collecting ducts. 56,57 Studies have also demonstrated Shroom3 mRNA expression in the pronephric tubules in zebrafish, the pronephric duct in Xenopus , and in the glomeruli of both. 5,58 RNA-sequencing in human adult tissue showed spatial expression of SHROOM3 transcripts in kidney glomeruli and tubules.…”
Section: Reviewmentioning
confidence: 99%
“…This altered recovery was due to disrupted Rho-kinase signaling and actin disorganization that resulted in disrupted epithelial differentiation of the tubular epithelium. 57 The changes in Shroom3 expression in heterozygous null mice could also have effects with age. The analysis of 1-year-old Shroom3 heterozygous null mice exhibit glomerulosclerosis and smaller podocytes with foot process flattening and effacement.…”
Section: Reviewmentioning
confidence: 99%